2018
DOI: 10.17533/udea.rfo.v30n1a8
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización De Las Acciones Inseguras en Odontología (Aio) en Una Institución De Docencia-Servicio, Medellín (Colombia), 2015-2017

Abstract: Introducción: con el fin de establecer acciones para mejorar la cultura de la seguridad del paciente en instituciones públicas y privadas, parece necesario contar con sistemas de vigilancia epidemiológica. Este estudio pretende caracterizar las atenciones inseguras en odontología (AIO) según diferentes variables, en una institución pública que forma recursos humanos en salud bucal en Medellín (Colombia). Métodos: estudio descriptivo longitudinal de las AIO reportadas en la Facultad de Odontología de la Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…14 Moreover, in a Colombian study, 541 reports were evaluated against unsafe acts in dentistry, and found that 14% of these incidents occurred in the endodontic clinics. 15 Medicine, particularly surgery, has long recognized the need to adopt patient safety initiatives by developing patient safety reporting systems to lessen the burden of iatrogenic harm. A few of the most important systems include the "World Alliance for the Safety of Patients," promoted by the WHO, and the Luxembourg Declaration of the European Union.…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, in a Colombian study, 541 reports were evaluated against unsafe acts in dentistry, and found that 14% of these incidents occurred in the endodontic clinics. 15 Medicine, particularly surgery, has long recognized the need to adopt patient safety initiatives by developing patient safety reporting systems to lessen the burden of iatrogenic harm. A few of the most important systems include the "World Alliance for the Safety of Patients," promoted by the WHO, and the Luxembourg Declaration of the European Union.…”
Section: Discussionmentioning
confidence: 99%